Pembelajaran Kewirausahaan di SMA Selama Pandemi Covid-19 - Leny Noviani; Adam Wahida (Jurnal Pendidikan Ekonomi (JUPE), 2022)
The objectives of this study are: 1) to describe the implementation of entrepreneurship learning in high school during the Covid-19 pandemic, and 2) to provide solutions on how to improve the quality of entrepreneurship learning. This study uses a descriptive method. Collecting data using a questionnaire. Respondents were 1,347 high school students in grades XI and XII from 10 high schools in Sragen The results showed that during the Covid-19 pandemic, entrepreneurship learning taught more about theory (69.1%). The method used by teachers when teaching is assignments (54.8%) on assignments/homework on entrepreneurship theory. The digital platforms used by teachers are google classroom (39.3%), zoom (9.6%, WhatsApp (25.5%), google meet (16%), and other platforms 9.5%. In general, students assessed that entrepreneurship lessons are in accordance with their needs and provide provisions to become entrepreneurs. As many as 64.5% of students feel enthusiastic about participating in lessons. Improvements in entrepreneurship learning according to students' perceptions are: the material is more applicable and interesting, trained in how to overcome real problems, and balanced with practice. Entrepreneurship education can be done through intra-curricular activities in class, co-curricular, and extra-curricular